Keanekaragaman Hayati sebagai Sumber Belajar Kontekstual dalam Kurikulum Pendidikan Biologi - Banyu Saputra; Arya Kertanegara Dharma; Gilang Prabaswara Kusuma (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
Biodiversity is an essential learning source in biology education, providing contextual and meaningful experiences for students. This study aims to explore the integration of biodiversity as a contextual learning source within the biology curriculum. The research employs a qualitative approach through literature studies and case studies in selected schools. Findings indicate that utilizing biodiversity in learning enhances students' ecological awareness, critical thinking, and problem-solving skills. Moreover, it fosters a sense of environmental responsibility. The study highlights the importance of developing instructional strategies that effectively integrate local biodiversity into the curriculum. These findings have significant implications for curriculum designers and educators in promoting contextual and sustainable biology learning.